KETERIKATAN INTERPERSONAL, TRAIT KEPRIBADIAN, DAN PEMAAFAN: SEBUAH KAJIAN TEORITIK - Nashori, H. Fuad (Jurnal Psikologi, 2011)
This article intends to explain the dynamics of individual forgiveness. The dynamics of forgiveness involves interpersonal attachment and personality trait. First, interpersonal attachment influences personality trait are agreeableness and neuroticism. Second, agreeableness and neuroticism personality trait influence forgiveness.